Počítačová hra pro boj se suchem v Unity - Olearčin, Daniel (Vysoké učení technické v Brně. Fakulta informačních technologií, 2022)
Táto bakalárska práca sa zaoberá návrhom a vývojom hry v hernom engine Unity. Hra má za úlohu byť edukatívna. Hráč má možnosť oboznámiť s rôznymi okolnosťami, ktoré vyplývajú na výnosnosť dediny a zádržnosť vody v krajine. Cieľom hry je mapovanie malej oblasti dediny, nad ktorou je možné vykonávať zamieňanie jednotlivých políčok za iné typy. Pomocou jednoduchých modelov, charakteristických výpočtov a pravidiel je možné sledovať dopad týchto zmien na výnosnosť dediny a zádržnosť vody v krajine.

This bachelor's thesis focuses on the design and development of the game in the Unity gaming engine. Game has the task of being educational. The player has the opportunity to familiarize himself with the different circumstances, which result on the profitability of the village and the retention of water in the country. The aim of the game is to map a small village above which it is possible to convert individual fields for other types. With simple models, characteristic calculations and rules, it is possible to monitor the impact of these changes on the profitability of the village and the retention of water in the country.
A Computer Game to Fight Drought in the Countryside in Unity
Keywords: Unity; Unity3D; Blender; C#; herné mechaniky; vysychanie krajiny; vývoj počítačovej hry; vývoj dediny v čase; herný dizajn; edukatívne hry; Unity; Unity3D; Blender; C#; game mechanics; drought of the country; computer game development; village development in time; game design; educational games